Heat-resistant barrier and ohmic contacts based on TiBx and ZrBx interstitial phases to microwave diode structures - Belyaev, A.E.; Boltovets, N.S.; Ivanov, V.N.; Kladko, V.P.; Konakova, R.V.; Kudryk, Ya.Ya.; Milenin, V.V.; Sheremet, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
We investigated thermal stability of Au–TiBx (ZrBx) barrier contacts, as well
as ohmic contacts with a TiBx diffusion barrier to n-Si (GaAs, InP, GaP, GaN, SiC). The
electrophysical measurements of Schottky barrier diodes and ohmic contacts were
performed both before and after rapid thermal annealing (RTA) up to 600 °С for the
structures on Si, GaAs, InP and GaP, as well as up to higher temperatures for GaN
(~900 °C) and SiC (~1000 °C). The concentration depth profiles of contact components
were taken using Auger electron spectrometry, while phase composition and surface
morphology of the metallization layers on test structures were determined using x-ray
diffraction and atomic force microscopy. It was shown that the silicon, indium
phosphide, gallium phosphide and gallium arsenide contact structures retained their
properties and layer structure after RTA up to 600 °С. Contact degradation occurred at a
temperature of 800 °С. The structures based on SiC (GaN) remained stable at temperatures
up to 1000 °С (900 °С).